Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jcm9040917
|View full text |Cite
|
Sign up to set email alerts
|

Thulium Laser Vapoenucleation of the Prostate (ThuVEP) in Men at High Cardiovascular Risk and on Antithrombotic Therapy: A Single-Center Experience

Abstract: Bleeding is the most common complication of transurethral resection of the prostate and simple open prostatectomy, especially in men on antiplatelet/anticoagulant therapy. The present study aimed to evaluate the safety and effectiveness of thulium laser vapoenucleation of the prostate (ThuVEP) for benign prostatic hyperplasia in patients on chronic antithrombotic medications. Between January 2015 and December 2019, 88 men underwent the procedure under antithrombotic agents in our center. The mean age was 74.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Additionally, the percentages of patients who needed electrocautery coagulation to control intraoperative bleeding were not significantly different between the three techniques, which also supports our claim that there are no significant differences in hemostatic effect between these techniques. The feasibility of laser ablation for BPH on anticoagulants was elucidated by previous studies 6,15,16 . During this trial, PVP, DVP, and ThuVAP were all performed without severe complications in patients on anticoagulants, suggesting a favorable safety profile for all of these techniques even in high‐risk patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Additionally, the percentages of patients who needed electrocautery coagulation to control intraoperative bleeding were not significantly different between the three techniques, which also supports our claim that there are no significant differences in hemostatic effect between these techniques. The feasibility of laser ablation for BPH on anticoagulants was elucidated by previous studies 6,15,16 . During this trial, PVP, DVP, and ThuVAP were all performed without severe complications in patients on anticoagulants, suggesting a favorable safety profile for all of these techniques even in high‐risk patients.…”
Section: Discussionmentioning
confidence: 74%
“…The feasibility of laser ablation for BPH on anticoagulants was elucidated by previous studies. 6,15,16 During this trial, PVP, DVP, and ThuVAP were all performed without severe complications in patients on anticoagulants, suggesting a favorable safety profile for all of these techniques even in high-risk patients.…”
Section: Discussionmentioning
confidence: 84%
“…A retrospective single-center study by Castellani et al assessed the safety and efficacy of ThuVEP in 88 men, mean age 74.7 with high cardiovascular risk and taking continuous antithrombotic therapy. 18 69.3% of the patients had an ASA score ≥3. Postoperative complications occurred in 26.1% of patients, with later complications occurring in 3.8% of patients.…”
Section: Resultsmentioning
confidence: 98%
“…There were three groups in the study and no patient showed TE. In a similar study, but with a smaller series, on Thulium Laser Vapoenucleation of the Prostate (ThuVEP), Castellani et al 15 pointed out two early admissions in the intensive care unit and one late myocardial infarction. In our study and the study of Castellani et al, the rate of patients with ASA[?…”
Section: Discussionmentioning
confidence: 94%